ABILITY OF BASIC SCHOOL TEACHERS IN THE DEVELOPMENT OF SIMPLE SCIENCE KIT BASED ON THE NATURAL ENVIRONMENT ON INUMAN SUB-DISTRICT - Zulhelmi Zulhelmi; Muhammad Nor; Fakhruddin Fakhruddin; Betty Holiwarni (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
The purpose of this training activity is to train the elementary school teachers in Inuman Sub-District, Kuantan Singingi Regency to developing an integrated  instrument component (IIC) natural science based on nature around. Teachers are trained to operate the Integrated Instrument Components natural science elementary shool that has been developed. The target audience is elementary school teachers in Inuman SubDistrict, Kuantan Singingi Regency and who attended this event came from public and private elementary school representatives with 29 participants from 12 schools. Method of activity is the presentation of materials, modeling, training and simulation /discussion. Evaluation carried out from the beginning of the activity, during the implementation and the end of activities with questionnaires, observations and interviews. Data were analyzed descriptively. The result of data analysis obtained by the average of the performance of 89% participants in very good category, so also the participant response about this service activity equal to 97,5% in very good category. The conclusion of the results of this training activities of elementary school teachers in the Inuman Sub-District, Kuantan Singingi Regency has the knowledge and able to implemeting in developing an integrated  instrument component simple natural science based on nature around for natural science learning in elementary school.